Debriefing for technology‐enhanced simulation: a systematic review and meta‐analysis. Issue 7 (July 2014) - Cheng, Adam; Eppich, Walter; Grant, Vincent; Sherbino, Jonathan; Zendejas, Benjamin; Cook, David A
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at 'discuss'